2006
DOI: 10.1109/iembs.2006.4398586
|View full text |Cite
|
Sign up to set email alerts
|

An Improved PID Switching Control Strategy for Type 1 Diabetes

Abstract: In order for an "artificial pancreas" to become a reality for ambulatory use, a practical closed-loop control strategy must be developed and critically evaluated. In this paper, an improved PID control strategy for blood glucose control is proposed and evaluated in silico using a physiologic model of Hovorka et al. [1]. The key features of the proposed control strategy are: (i) a switching strategy for initiating PID control after a meal and insulin bolus; (ii) a novel time-varying setpoint trajectory, (iii) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Among its pros, there is the possibility of relating the PID tuning parameters to the biometric parameters of the patient [259]–[261]. …”
Section: Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Among its pros, there is the possibility of relating the PID tuning parameters to the biometric parameters of the patient [259]–[261]. …”
Section: Controlmentioning
confidence: 99%
“…As already mentioned, in order to improve performance, a possibility is to add a feedforward action, so as to recover the promptness of meal compensation. Although MPC strategies appear better suited to incorporate predictions on the future effects of meals, an attempt has been made along this direction by [261], where the authors present a controller switching between PID regulation and bolus administration in proximity of meals. In any case, irrespective of the adopted tuning procedure or the presence of a feedforward action, PID controller will be subject to saturations and therefore an anti-windup implementation is always needed.…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the risk caused by great changes of blood glucose and preventing from hypoglycemia and hyperglycemia, the controller are always being optimized and promoted. Among them, PI controllers by Gantt et al (2007), PID by Switching Marchetti (2008) [3]; Sliding mode by Hernandez (2013), MPC method by Sorru et al (2012) can be mentioned [1]. In PI method, a sensor and subcutaneous injection pump were used and it is a function of output error.…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms suffered from being too patient specific, being sensitive to measurement noise, and in having to be reprogrammed as the patient’s metabolic parameters changed. A recently proposed PID switching algorithm by Marchetti et al [6] was demonstrated to perform favorably when faced with meal disturbances, changes in insulin sensitivity, and intra-patient variability in simulations. Among advanced algorithms, Fisher [7] and Ollerton [8] developed optimal control algorithms, but the authors demonstrated the inability of their algorithms alone to successfully control glucose through simulations.…”
Section: Introductionmentioning
confidence: 99%